Engineered extracellular vesicles: a breakthrough approach to overcoming sperm cryopreservation challenges - Abazar Esmaeili; Vahid Esmaeili; Abdolhossein Shahverdi; Mohamadreza Baghaban Eslaminejad (Reproductive Biology and Endocrinology)
Abstract Freezing sperm for artificial insemination (AI) has been common for decades, but this method causes damage to sperm, which affects its viability and fertility. Various strategies have been used to treat sperm cryopreservation complications, but their results are still not satisfactory. The latest approach in this field is using extracellular vesicles (EVs). The role of EVs in reproduction, such as spermatogenesis, sperm capacitation, and fertility has been proven. EVs can deliver proteins, lipids, nucleic acids, and other molecules to the sperm for repair. The EVs carry proteins, lipids, nucleic acids, and other molecules, which could be involved in sperm quality, functionality or fertility. The application of EV derived from animal and human cell sources for cryoinjury treatment indicates the improvement of sperm quality after freeze-thawing. In addition, different EV engineering methods regarding various EV cargos could be more influential for cryopreserved sperm treatment because they could provide EV customized content for delivering to cryoinjured sperm, according to their unique needs to enhance viability and fertility. In this review, first, we reminded the sperm cryopreservation complications, and next explained the conventional and modern strategies for overcoming them. Then, we have pointed out the role of EV in sperm development and the following mentioned the study results of using EV from different cell sources in sperm cryoinjuries repair. Also, we suggested several predisposing molecules (including microRNAs and proteins) for EV engineering to treat sperm cryopreservation complications by indirect engineering procedure, including genetic manipulation and incubation with therapeutic molecules, and direct engineering procedure, including electroporation, sonication, incubation, saponin permeabilization, extrusion, CaCl2-heat shock, and freeze/thawing. Finally, we discussed the limitations of EV application and ethical considerations in this context. In the meantime, despite these limitations, we pointed out the promising potential of the EV engineering strategies to reduce infertility rates by helping to overcome sperm cryopreservation challenges.